Increasing preexposure prophylaxis use and 'net prevention coverage' in behavioural surveillance of Australian gay and bisexual men. (1st April 2021) - Holt, Martin; Broady, Timothy R.; Mao, Limin; Chan, Curtis; Rule, John; Ellard, Jeanne; O'Donnell, Darryl; Grulich, Andrew E.; Prestage, Garrett; Bavinton, Benjamin R.
Abstract : Objective(s): To assess trends in HIV prevention strategies among Australian gay and bisexual men (GBM) since the introduction of preexposure prophylaxis (PrEP), the level of net prevention coverage (the use of safe strategies), and the characteristics of HIV-negative and untested GBM who remain at risk of HIV. Design: Repeated behavioural surveillance of GBM recruited from venues, events and online in seven Australian states and territories. Methods: Participants with casual male partners were included. Trends in sexual practices, prevention strategies, net prevention coverage and the characteristics of 'at risk' participants were assessed with binary and multivariate logistic regression. Results: A total of 32 048 survey responses (2014–2019) were included. The proportion of participants who reported consistent condom use declined (44.6–23.2%). The proportion who reported any condomless anal intercourse with casual partners increased (37.4–62.0%) but net prevention coverage also increased (68.1–74.9%), with higher levels of undetectable viral load among HIV-positive participants and rapidly increasing PrEP use by HIV-negative participants. PrEP became the most commonly reported prevention strategy in 2019 (31.1%). The analysis of 'at risk' participants showed that they became more likely to report frequent condomless anal intercourse with casual partners but had fewer partners and more partners with undetectable viral load or on PrEP. 'At risk' participants became more likely to identify as bisexual and to be born overseas. Conclusion: There has been a rapid, historic shift in HIV prevention among GBM in Australia. Net prevention coverage has increased among GBM and 'at risk' GBM have become less at risk of HIV, facilitating reductions in HIV transmission. Abstract : Supplemental Digital Content is available in the text